Lexicography, terminology, and translation : text-based studies in honour of Ingrid Meyer - Meyer, Ingrid; Bowker, Lynne (Perspectives on translation., 2006)
This volume in honour of Ingrid Meyer is a tribute to her work in the interrelated fields of lexicography, terminology and translation. One key thing shared by these fields is that they all deal with text. Accordingly, the essays in this collection are united by the fact that they too are all "text-based" in some way. In the majority of essays, electronic corpora serve as the textual basis for investigations. Chapters focusing on electronic corpora include a description of a tool that can be used to help build specialized corpora in a semi-automatic fashion; corpus-based investigations of term